2012
DOI: 10.1021/la204628c
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Superparamagnetic Iron Oxide Nanoparticles at Different pH Values: Experimental and Theoretical Analysis

Abstract: The detection of superparamagnetic nanoparticles using NMR logging has the potential to provide enhanced contrast in oil reservoir rock formations. The stability of the nanoparticles is critical because the NMR relaxivity (R(2) ≡ 1/T(2)) is dependent on the particle size. Here we use a molecular theory to predict and validate experimentally the stability of citric acid-coated/PEGylated iron oxide nanoparticles under different pH conditions (pH 5, 7, 9, 11). The predicted value for the critical surface coverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 29 publications
2
54
0
Order By: Relevance
“…[12] Briefly, iron(III) tri(acetylacetonate) [Fe(acac) 3 ] (2 mmol), benzyl ether (40 mL), 1,2-tetradecanediol (10 mmol), oleic acid (6 mmol), and oleylamine (6 mmol) were mixed and stirred magnetically under a flow of nitrogen. The mixture was heated at 2 degrees per min to 100 °C and kept for 45 min, followed by heating to 200 °C at 2 degrees per min and kept for 2 h. Subsequently the reaction mixture was heated to reflux (∼ 300 °C) and held for another 30 min to 1 h. The oleic acid – coated SPIONs were stored after washing steps with an excess of ethanol and after a drying step in a vacuum oven.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Briefly, iron(III) tri(acetylacetonate) [Fe(acac) 3 ] (2 mmol), benzyl ether (40 mL), 1,2-tetradecanediol (10 mmol), oleic acid (6 mmol), and oleylamine (6 mmol) were mixed and stirred magnetically under a flow of nitrogen. The mixture was heated at 2 degrees per min to 100 °C and kept for 45 min, followed by heating to 200 °C at 2 degrees per min and kept for 2 h. Subsequently the reaction mixture was heated to reflux (∼ 300 °C) and held for another 30 min to 1 h. The oleic acid – coated SPIONs were stored after washing steps with an excess of ethanol and after a drying step in a vacuum oven.…”
Section: Methodsmentioning
confidence: 99%
“…The polyethylene glycol (PEG) coating of SPIONs provides stability between the particles via steric repulsion, [12] and reduces undesired interactions with plasma proteins and their subsequent opsonization. [13] PEG also allows targeting ligands to be conjugated onto the SPIONs.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest challenges for using IO NPs for oil reservoir applications lie in (i) synthesizing a IO NP core with high initial magnetic susceptibility which make it possible to generate enough signal for mapping under even low external magnetic field, and (ii) developing a surface coating procedure which enable the IO NPs to be stable in the subsurface oil reservoir environment, namely high temperature, high salinity aqueous solutions. Recently, long term colloidal stability of IO and other NPs was reported even over a wide pH range in high salinity, high temperature brines typically encountered in oil reservoirs [10][11][12][13][14][15][16] . For example polymers containing 2-acrylamido-2-methylpropane sulfonic acid (AMPS), which bind weakly to Ca 2+ , remain extended after coated on ~100 nm IO nanoclusters in American Petroleum Institute brine (API brine, 8% w/w NaCl + 2% w/w CaCl 2 , anhydrous basis) and provide efficient steric and electrostatic stabilization [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Different researchers studied the diameter stability of magnetic nanoparticles and degradation stability by using dynamic light scattering (DLS) [27] and inductively coupled plasma (ICP) [28]. Yoonjee Park and his research group showed that the effective diameter for citric acid-coated/PEGylated iron oxide nanoparticles did not increase at pH 7 or 9 after 30 days but increased at pH 11 [27].…”
Section: Introductionmentioning
confidence: 99%
“…Yoonjee Park and his research group showed that the effective diameter for citric acid-coated/PEGylated iron oxide nanoparticles did not increase at pH 7 or 9 after 30 days but increased at pH 11 [27]. Similarly Hoskins showed that magnetic nanoparticles coated with poly ethylenimine and poly ethylene glycol were stable at neutral pH and at an acidic environment at a pH of 4.6 in the presence of sodium citrate [28].…”
Section: Introductionmentioning
confidence: 99%